2014
DOI: 10.5897/sre2014.5819
|View full text |Cite
|
Sign up to set email alerts
|

The effects of humic acid application upon the phosphorus uptake of the tomato plant (Lycopersicum esculentum L.)

Abstract: Humic acid can transform mineral nutrients into available forms for the plants. High lime content, low organic matter content, high pH, low moisture content and insufficient profile characteristics all higher plant phosphorus uptakes and consequently regress plant growth and development. The present research was conducted to investigate the effects of humic acid treatments (H.A.) (0, 60, 120 mg/kg) on phosphorus use efficiency (PUE) (0, 50, 100 mg/kg P) of grape and pole tomato (Lycopersicum esculentum L.) var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Regarding the combinations between organic substances and chelating agents, the treatment of HA+ citric acid was superior in giving high extractable amount of P in soil, followed by HA+ EDTA in most physiological stages of growing bean plants, with significant differences in the presence of added bacteria. Humic acid plays a vital role in increasing P availability in soil (Doran et al, 2003;Sahin et al, 2014), plus its considerable content of P (Table 1a). Citric acid, in addition to decrease soil pH, it makes complexes with Ca forming calcium citrate and releasing P in soluble form in the soil (Drouillon & Merckx, 2003).…”
Section: Available P In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the combinations between organic substances and chelating agents, the treatment of HA+ citric acid was superior in giving high extractable amount of P in soil, followed by HA+ EDTA in most physiological stages of growing bean plants, with significant differences in the presence of added bacteria. Humic acid plays a vital role in increasing P availability in soil (Doran et al, 2003;Sahin et al, 2014), plus its considerable content of P (Table 1a). Citric acid, in addition to decrease soil pH, it makes complexes with Ca forming calcium citrate and releasing P in soluble form in the soil (Drouillon & Merckx, 2003).…”
Section: Available P In Soilmentioning
confidence: 99%
“…Regarding the interaction between solubilizing agents, the treatment of HA+ EDTA, followed by that plus citric acid gave the highest concentration of P in plant leaves, with significant difference as compared to the other treatments. Sahin et al (2014) found that humic substances in interaction with P in the soil could decrease the P-fixation and increase the P-uptake by plants.…”
Section: N P and K Concentrations In Faba Bean Leavesmentioning
confidence: 99%